Inflammatory and diabetic conditions trigger SHP2 tyrosine phosphatase expression and subsequent aberrant activation of primary human monocytes. (3rd October 2022) - Dorenkamp, M; Nasiry, M; Koch, S; Semo, D; Loeffler, I; Wolf, G; Reinecke, H; Godfrey, R
Abstract: Purpose: Atherosclerosis is an inflammatory process that is particularly accelerated in diabetics, leading to increased incidence of cardiovascular diseases such as CAD and PAD in diabetic patients. Monocytes are the main component of atherosclerosis development. SHP-2 tyrosine phosphatase has been identified as an important regulator of monocyte function. The present study therefore aims to investigate the regulation of SHP-2 in inflammatory and diabetic conditions. Methods: Primary human monocytes were isolated from the peripheral blood of type 2 Diabetes mellitus (T2DM) patients and healthy individuals. Monocytes were incubated with pro-inflammatory cytokine TNFa. For diabetic conditions, monocytes were incubated with methylglyoxal (MG), a highly reactive side product of glycolysis, or Receptor for advanced glycation end product (RAGE) ligand AGE-bovine serum (AGE-BSA). Monocyte migration was studied with Transwell migration assays. Expression of important molecules was investigated with Western Blot, RT-qPCR or FACS. Pharmacological inhibitors for SHP2, RAGE or NFκB were used. Results: First, we could detect a significant correlation between SHP-2 mRNA and TNFa levels in T2DM monocytes in comparison to monocytes from healthy individuals. In line with that, incubation of monocytes with TNFa lead to an enhanced expression of SHP-2. Co-incubation with NFκB-inhibitor blocked TNFa-induced SHP-2 upregulation. Interestingly, incubation of monocytes with methylglyoxal caused increased release of TNFa and also augmented expression of SHP-2, indicating a pro-inflammatory effect of diabetic conditions. Moreover, AGE-BSA treatment induced enhanced SHP-2 expression, reflecting an inflammatory-independent pathway which regulates SHP-2 additionally. This could be supported by the observation that pharmacological inhibition of RAGE attenuated both AGE-BSA and MG-induced SHP-2 activation. On a functional level, increased expression of SHP-2 in each treatment resulted in a pro-migratory phenotype that could be completely reversed by inhibition of RAGE, respectively. Fittingly, monocytes from T2DM patients showed increased migration, which normalized to an ordinary level after application of a SHP-2 inhibitor. Conclusions: The present results reveal a new mechanism for accelerated atherosclerosis development in diabetic patients. MG and advanced glycated end products, as crucial components of the diabetic milieu, lead to increased expression of SHP-2 via the RAGE-NFkB signalling axis. Interestingly, this diabetic environment causes an increased inflammatory response through the release of TNFa cytokine, which itself leads to enhanced SHP-2 expression through activation of the NFkB transcription factor. Finally, by pharmacological inhibition of each component in this outlined SHP-2 regulatory pathway, we were able to prevent the pro-migratory activation of monocytes, offering a new approach to the treatment of diabetes-induced atherosclerosis. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): IZKF SEED Project 14/20